Hubungan antara Kekuatan Otot Lengan dengan Akurasi Memanah dalam Olahraga Panahan - Novian, Geraldi; Komarudin, Komarudin; Rismayadi, Alen; Nursaba, Siti; Sopandi, Salma Maharani (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Archery has a goal: to release an arrow to the center point of the intended target and master perfect archery techniques that will produce complex and beautiful movements. In addition, archery also requires consistent movements, practice, and competition. This study examines the relationship between arm muscle strength and archery accuracy. This study is a descriptive study involving 10 archery athletes from West Java. The pull hand-held dynamometer instrument and a 10-meter archery accuracy test were used in this study. The Shapiro-Wilk test and Spearman rank correlation were used for data analysis. The study showed a significant relationship between arm muscle strength and archery accuracy. In can be concluded that there is a substantial relationship with a weak and unidirectional correlation between arm muscle strength and archery accuracy. The author sees that arm muscle strength is related to archery accuracy, so arm muscle strength must be trained as well as possible to achieve a high archery accuracy score.